PENGARUH IKLAN MEDIA SOSIAL TERHADAP MINAT PEMBELIAN DENGAN VARIABEL INTERVERNING PERSEPSI KONSUMEN PADA OBJEK PRODUK BEAUTY & SKIN CARE EMINA PLATFORM E-COMMERCE - Alvi, Alvi; Meta, Williya; Setyorini, Dian (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The trend of online shopping in Indonesia shows significant growth potential, with beauty products accounting for one of the largest proportions of transactions. The second-largest group of online buyers consists of adolescents aged 18 to 25, aligning with the target market of EMINA products, which are specifically aimed at young consumers. This study aims to analyze the influence of advertising on consumer purchase intention of EMINA beauty & skin care products on e-commerce platforms, with consumer perception serving as an intervening variable. The sampling technique used in this study is snowball sampling, involving 66 female respondents aged 18 to 25 in the city of Pekanbaru. The research applies a quantitative method using multiple linear regression analysis processed through Smart PLS version 4.0. The results of the study show that: (1) Social media advertising has a positive and significant influence on consumer perception by 46.5%, with the remaining 53.5% influenced by other factors; (2) Advertising has a positive and significant influence on purchase intention by 88.2%, with 11.8% influenced by other factors; (3) Consumer perception has a positive and significant influence on purchase intention by 50%, with the remaining 50% influenced by other factors; and (4) The influence of social media advertising on purchase intention is direct, and consumer perception does not serve as a mediating variable in the case of EMINA Beauty & Skin Care products on e-commerce platforms.Keyword: Emina, Social Media Advertising, Purchase Intention, Consumer Perception.Abstrak: Trend belanja online di Indonesia memiliki potensi pertumbuhan besar, salah satu proporsi transaksi terbesar ialah produk kecantikan, jumlah pembeli transaksi online terbesar kedua kategori remaja (usia 18 s.d 25 tahun) hal ini sejalan dengan target konsumen produk EMINA untuk anak remaja. Pada penelitian ini bertujuan untuk melakukan analisis pengaruh advertising terhadap minat beli konsumen pada produk EMINA beauty & skin care di platform e-commerce melalui persepsi konsumen sebagai variable interverning. Metode pengambilan sample penelitian menggunakan tekhnik Snowball sampling pada 66 orang responden wanita usia 18 s.d 25 tahun kota pekanbaru. Metode penelitian ini menggunakan analisis kuantitatif regresi linier berganda menggunakan alat pengelohan Smart PLS versi 4.0. Hasil penelitian menunjukkan bahwa 1). Iklan Media Sosial berpengaruh positif dan signifikan terhadap Persepsi Konsumen sebesar 46,5% dan sisanya dipengaruhi oleh faktor lain, 2) Advertising Berpengaruh positif dan signifikan terhadap Minat Pembelian sebesar 88,2% dan sisa 11,8% dipengaruhi oleh faktor lainnya dan, 3) Persepsi Konsumen berpengaruh positif dan signifikan terhadap Minat Pembelian sebesar 50% dan sisanya 50% dipengaruhi oleh faktor lain . 4.Pengaruh Iklan Media Sosial terhadap berpengaruh terhadap Minat Pembelian dan variable Perspsi Konsumen bukan sebagai Mediasi produk Emina Beauty & Skin Care di platfor e- commerce.Kata kunci: Emina, Iklan Media Sosial, Minat Pembelian, Persepsi Konsumen